2011
DOI: 10.4093/dmj.2011.35.4.374
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations between Extremity Circumferences with Total and Regional Amounts of Skeletal Muscle and Muscle Strength in Obese Women with Type 2 Diabetes

Abstract: Background: Insulin resistance is related to central obesity and the amount of skeletal muscle. A simple and practical anthropometric marker for muscle mass is not known, although waist circumference (WC) is used as an indicator of abdominal obesity. The aims of this study were to investigate whether arm (AC) and thigh circumferences (TC) can be used as an indicator of muscle mass and if they are related to muscle strength. Methods: A total of 110 obese (body mass index [BMI]≥25 kg/m 2 ) women with type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
9
1
2
Order By: Relevance
“…The inconsistent association of TC compared to CC may be due to higher fat content of thigh muscles. The findings of our study is supported by previous study by Kwon et al which showed that TC has significant but poor correlations with total muscle mass compared to mid arm circumference [28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The inconsistent association of TC compared to CC may be due to higher fat content of thigh muscles. The findings of our study is supported by previous study by Kwon et al which showed that TC has significant but poor correlations with total muscle mass compared to mid arm circumference [28].…”
Section: Discussionsupporting
confidence: 93%
“…There is good correlation of all circumference measures with muscle mass, and the correlation is independent of weight, height, and BMI [26][27][28]. Several previous studies have shown significantly strong positive association of lean muscle mass with BMD at hip and spine in both genders and hip geometry in male.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Waist circumference correlates with fat mass, and mid-upper arm circumference correlates more strongly with muscle mass. [13,14] …”
Section: Methodsmentioning
confidence: 99%
“…Kwon et al (2011) salientam a associação da circunferência da coxa ao metabolismo da glicose e resistência à insulina.…”
Section: Estado Nutricional E Composição Corporalunclassified